1964
DOI: 10.1037/h0044398
|View full text |Cite
|
Sign up to set email alerts
|

Job attitudes in management: V. Perceptions of the importance of certain personality traits as a function of job level.

Abstract: This study investigated managers' perceptions of the relative importance of 10 personality traits for success in their managerial roles, as a function of level of position within management. Data were obtained by means of a questionnaire in which the 10 traits were rank ordered in importance by over 1800 respondents from all parts of management and all types of companies. The 10 traits consisted of 5 Other-Directed or Organization Man type traits, and 5 Inner-Directed type traits. Results showed that Inner-Dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

1966
1966
1994
1994

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 3 publications
(5 reference statements)
0
14
1
Order By: Relevance
“…The findings support neither Porter's (1963), Porter and Henry's (1964), nor El Salmi and Cummings' (1968) findings regarding the interactive effects of organization size and level. Here, higher rank is associated with more positive responses regardless of ship size.…”
Section: Data Analysis and Resultscontrasting
confidence: 68%
See 1 more Smart Citation
“…The findings support neither Porter's (1963), Porter and Henry's (1964), nor El Salmi and Cummings' (1968) findings regarding the interactive effects of organization size and level. Here, higher rank is associated with more positive responses regardless of ship size.…”
Section: Data Analysis and Resultscontrasting
confidence: 68%
“…Previous research on organizational level and attitudes has generated conflicting results. Porter (1963Porter ( , 1964 found that higher-level personnel are more satisfied in large organizations, while lower-level managers are more satisfied in smaller organizations. El Salmi and Cummings (1968) found just the opposite.…”
Section: Hypothesesmentioning
confidence: 99%
“…As regards the need-fulfilment measure, a pilot study in which the scale was administered individually to a comparable sample (which gave them an opportunity to comment on each item) revealed that they had no difficulty in understanding the various items. In addition, the fact that this scale has been used successfully in a variety of jobs and been found to relate highly to a number of relevant external criteria (Porter, 1962(Porter, , 1963Porter and Henry, 1964;Porter and Mitchell, 1967) suggests that it should be pretty valid in the present context. That the scale was simply used to obtain an overall score for each S is supported; by a recent factor analytic study (Herman and Hulin, 1973) which found that a single dimension, rather than five separate dimensions (for each of the needs covered by the scale) could best account for the score variance.…”
Section: Resultsmentioning
confidence: 94%
“…The prototype of the questionnaire used in this study as well as the rationale employed in its construction have been reported in detail elsewhere by Porter and Henry (1964). Briefly, Porter and Henry used 10 traits in their analysis and these traits pertain to a composite personality dimension composed of related but slightly different personality continua?…”
Section: Ques Tionnuirementioning
confidence: 99%
“…Although labor unions have a wide sphere of influence within the American economy, little is known about those who manage the activities of these national labor unions. This is indeed startling in view of the current interest in the subject of management and those who occupy management jobs (See Rosen & Weaver, 1960;Porter, 1964). The national union official in the fullest sense of the word is a manager too.…”
mentioning
confidence: 99%